Therapeutic effect of alendronate in an experimental temporomandibular joint osteoarthritis. (7th December 2022) - Acibadem, Elif; Keskinruzgar, Aydin; Bozdag, Zehra; Yavuz, Gunay Yapici
Abstract: Background: Temporomandibular joint osteoarthritis is a common degenerative joint disease. This disease negatively affects the daily life, speech and chewing functions of patients. Objective: This study aimed to evaluate the effects of intra‐articular injection of alendronate to osteoarthritis, which has a protective effect on bone and cartilage tissue and helps reduce inflammation in temporomandibular joint osteoarthritis. Methods: A total of 24 Wistar albino rats were used in the study. Rats were divided into four groups: study, saline, control and sham. In both saline and control groups, monosodium iodoacetate was injected intra‐articularly to induce osteoarthritis. Alendronate was administered intra‐articularly to the study group weekly for 4 weeks. In the saline group, saline was administered by intra‐articular injection. At the end of the 12th week, all groups were sacrificed. Mandibular condyle tissues were examined histopathologically. Results: According to the results, osteoarthritic changes in the control group were higher than those in the study group ( p < .05). No significant reduction in osteoarthritic changes was observed in the saline group ( p > .05). Significant osteoarthritis findings were observed in all groups compared with the sham group ( p < .05). Conclusion: Intra‐articular injection of alendronate was found to have positive results on TMJ osteoarthritis. In addition, it was seen that alendronate has effects on reducing cartilage tissue degeneration and loss of matrix proteins. Abstract : This study aimed to evaluate the effects of intra‐articular injection of alendronate to osteoarthritis, which has a protective effect on bone and cartilage tissue and helps reduce inflammation in temporomandibular joint osteoarthritis.